Carried Couples Participation in Online Business: A Study of Harmonious Family Formation - Nawa Azkiya, Rahima (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
The high divorce rate in Indonesia indicates a lack of harmony in the household. Divorce is motivated by various factors, the highest factor at this time is the dispute and quarrel factor and economic factors. This qualitative study includes field research (Field Research), data collection techniques with interviews, and documentation of women as housewives and online business owners in the Pujut sub-district, Central Lombok district, West Nusa Tenggara. The results showed that online business provides many positive impacts for housewives in the Pujut sub-district of Central Lombok, such as increasing income for daily needs, adding relationships and insights about business, reducing boredom, becoming more independent, and good time and financial management. In addition, the housewives also receive support from their spouses and families which has a big impact on their business, helping each other, participatory cooperation, fairness, and mutual benefit in developing the company so that it still exists today. This is in line with the principle of Mubadala, which emphasizes partnership or equality between men and women in life, especially family life.